Descriptive Study: Psychosocial Conditions of Nurses Handling Patients with Covid 19 - Heri Setiawan; Sumawan Sumawan; Adi Dwi Pramono (Jurnal Ilmu Keperawatan Jiwa, 2021)
The COVID 19  pandemic has an impact on all aspects of life, including nurses in hospitals who treat COVID 19  patients. The impact of COVID 19  is not only on the physical aspect but also on psychosocial problems. The psychosocial impact of COVID 19  on nurses is due to the risk of being infected and the perception that they can infect other people, the use of PPE, stigma in society, and changes to health protocol guidelines. This study used a descriptive technique with a total sampling of 31 nurses. The questionnaire used is the SRQ-29. The results of this study indicate that the mental emotional conditions of the nurses who handled the suspected COVID 19  and COVID 19  confirmation patients were mostly in good health or did not experience symptoms of mental emotional disorders amount  29 nurses (93.55%). In the questionnaire related to the use of psychoactive substances, most nurses did not use psychoactive substances, amount 31 nurses (100%). On the questionnaire related to psychotic symptoms, most of them did not experience psychotic symptoms amount 31 nurses (100%). In the PTSD symptom questionnaire, most of them did not experience PTSD symptoms, amount 22 nursesc (71.97%).